2000
DOI: 10.1002/pc.10181
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐Dependent function in the correlation between hardness and yield stress of polyethylene composites

Abstract: A study of the validity of a correlation between compressive yield stress and Vickers hardness of CaCO,/high density polyethylene composites was carried out. Composites with calcium carbonate in the range of 0-0.40 were produced by twin screw extrusion followed by compression molding. Hardness was implemented by indenting the samples with Vickers indenter and compression test were carried out at various crosshead speeds in the range of 0.2-50 mm mir-' . It was found that increasing calcium carbonate content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…For a PP/PE blend system it was shown that this is not the case [13]. Considering the correlation of Vickers hardness and compressive yield stress, however, Tabor's rule may still be valid [14]. Our first attempts show a comparable strain rate dependency of yield stresses and Martens hardness in the range 10 −5 –0.1 and 0.0015–0.15 s −1 , respectively, for PVDF and PC.…”
Section: Resultsmentioning
confidence: 76%
“…For a PP/PE blend system it was shown that this is not the case [13]. Considering the correlation of Vickers hardness and compressive yield stress, however, Tabor's rule may still be valid [14]. Our first attempts show a comparable strain rate dependency of yield stresses and Martens hardness in the range 10 −5 –0.1 and 0.0015–0.15 s −1 , respectively, for PVDF and PC.…”
Section: Resultsmentioning
confidence: 76%
“…However, reinforcing materials such as glass fibers, carbon fibers, and aramide fibers are not biodegradable. Among the various reinforcing materials, CaCO 3 is attractive because of its low cost 12–19. Another advantage of CaCO 3 is derived from its hydrophilic behavior, that is, its water adsorption characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Calcite is the thermodynamic stable phase and generally is in rhombohedral form. Morphology and properties of CC vary with their polymorphism.…”
Section: Introductionmentioning
confidence: 99%